Praktik Otoritarianisme dalam Demokrasi Indonesia Pasca Reformasi: Analisis Konstitusional dan Politik: Authoritarian Practices in Post-Reform Indonesia’s Democracy: A Constitutional and Political Analysis - Muchamad Dicky Rachmawan; M Yahya Wahyudin (SIYASI: Jurnal Trias Politica, 2024)
Democracy does not operate without flaws. Although it represents the best concept of governance among the worst, democracy always contains the potential to lead toward authoritarian regimes. The problem of authoritarianism is a social psychology issue concerning a regime type that suppresses popular sovereignty. In various countries that have experienced it, authoritarianism does not emerge on its own; there are preconditions that can be analyzed based on the ongoing socio-political context, including in post-reform Indonesia. To demonstrate how authoritarian practices operate in Indonesia, this research employs a literature study approach, as its focus relies on sources derived from literature. The research findings indicate that symptoms of authoritarianism such as abusive constitutionalism practices, electoral cartelized systems, juristocracy, and autocratic legalism have occurred in Indonesia, reinforced by various factors such as the formation of legislation that disregards constitutional principles, electoral autocracy, and the partiality of judicial power to the political will of those in power. There are several recommendations for rebuilding Indonesian democracy to make it better, including legal reforms on limiting Presidential powers before elections, tightening ethical oversight of judges, strengthening the authority of state institutions that have been weakened, and encouraging parliament to undertake transformative legislature in order to implement democracy more substantively.